Experimental study on interaction, shock wave emission and ice breaking of two collapsing bubbles. (25th August 2020) - Cui, Pu; Zhang, A-Man; Wang, Shi-Ping; Liu, Yun-Long
Abstract : Abstract : In this work ice breaking caused by a pair of interacting collapsing bubbles was studied by an experimental approach. The bubbles were generated by an underwater electric discharge simultaneously, positioned either horizontally or vertically below a floating ice plate and observed via high-speed photography. The bubble-induced shock waves, which turn out to be crucial to the fracturing of the ice, were visualized using a shadowgraph method and also measured using pressure transduces. Unique bubble behaviour was observed, including bubble coalescence, bubble splitting, inclined counter-jets and asymmetric toroidal bubble collapse. Bubble dynamic properties, such as jet speed, jet energy and bubble centre displacement, were measured. Shock wave emission and ice breaking capability of the two bubbles were investigated over a range of inter-bubble and bubble–boundary distances. Regions where the damaging potential of the bubble pair are strengthened or weakened were summarized and possible reasons for the variation in the ice breaking capability were analysed based on bubble morphology, jet characteristics and shock wave pressure. The findings may contribute to more efficient ice breaking and also inspire new ways to manipulate cavitation bubble damage.